2000
DOI: 10.1177/154193120004402251
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Urgency in Speech Warnings

Abstract: Two experiments are reported that investigate the effects of acoustics and semantics in verbal warnings. In the first experiment subjects rated the urgency of warning signal words spoken in different presentation styles (URGENT, NON-URGENT, MONOTONE). Significant differences in urgency ratings were found between presentation styles. Acoustic analysis revealed how acoustic parameters differed within these different presentation styles. These acoustic measurements were used to construct synthesised speech warnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Thus speakers are able to imbue an appropriate emotion into their utterance, and listeners are able to interpret this expression accurately. Similar results are shown elsewhere (Hellier et al, 2002;Barzegar & Wogalter, 1998a, Hollander & Wogalter, 2000Weedon et al, 2000;Edworthy et al, 2000) for a single measurement of perceived urgency or arousal strength. The study reported here also shows that the related dimensions of appropriateness and believability show more or less the same effects.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus speakers are able to imbue an appropriate emotion into their utterance, and listeners are able to interpret this expression accurately. Similar results are shown elsewhere (Hellier et al, 2002;Barzegar & Wogalter, 1998a, Hollander & Wogalter, 2000Weedon et al, 2000;Edworthy et al, 2000) for a single measurement of perceived urgency or arousal strength. The study reported here also shows that the related dimensions of appropriateness and believability show more or less the same effects.…”
Section: Discussionsupporting
confidence: 87%
“…Some words are perceived as being more urgent, believable and appropriate than are others. In general the effects for signal word on perceived urgency are similar to those found else where for text and spoken presentation (Barzegar & Wogalter, 1998aHollander & Wogalter, 2000;Weedon et al, 2000) and similar to those found when natural speech was used in Experiment 1. Where there are differences between natural and synthetic speech in the rank order of the words, they appear to be a result of the softness of the articulation, which is only given appropriate emphasis in natural speech.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Since many warning characteristics may combine to creating a subjective warning utility, we reviewed warning characteristics that may influence the effectiveness of warnings. To our best knowledge, we find that the following warning characteristics could influence the warning effectiveness: Category one is regarding warning effectiveness in representing the hazard/task: Representation of Event Urgency [30][31][32], the degree to which the event urgency is represented by a warning; Time to Display [33], the degree to which a warning occurs at a favourable time; Number of Replications [34]; Distinctive Features [35], the degree to which a warning can be differentiated from other warnings in the system. Category two is regarding features relevant to the warning itself: Modality [36], the way a warning is presented; Loudness [37], the attribute of auditory sensation in terms of which sounds can be ordered on a scale extending from quiet to loud; Length of the Warning, the number of words in a warning; Voice Type, whether a warning is presented with a female or male voice [38]; Voice Quality [34], the degree to which a warning can be recognized; Rate of Speech, the number of words presented in terms of time.…”
Section: 12mentioning
confidence: 99%
“…Urgencyi si nt his case conceiveda sa na uditory attribute of the sound. Signals made of bursts of harmonic pulses (after [7])a nd speech signals [15,16] were studied. The results of such experiments are mathematical relationships between perceivedurgencyand acoustical properties (the more urgent signals are high in pitch, with short transients, partials with random frequencies, and an irregular rhythm).…”
Section: Warning Signalsmentioning
confidence: 99%